Management under uncertainty: the impacts of Covid-19 and corporate foresight on innovation in finnish companies - Paula, Caio Cardoso de (2022)
The role that corporate foresight has on organizational ambidexterity - an organizations capability to simultaneously innovate incrementally and radically - within an uncertain external environment is the main topic of this research thesis. While it is believed that corporate foresight has a positive impact on ambidexterity, little is known through which mechanisms this impact takes place specially in an uncertain environment. In other words, how does a capability as an antecedent lead to organizational ambidexterity in complex scenarios. With recent developments in this research field, this study proposed a new conceptual model that introduces corporate foresight as a capability and enables scholars to conduct a qualitative research inspecting the causal links of the use of corporate foresight and an organization's ability to innovate within the context of extreme uncertainly. In order to do so, this study propose the analysis of three Finnish companies that underwent impacts of the COVID-19 pandemic and were able to use its corporate foresight capabilities to generate radical and incremental innovations.